Suppression of mechanical hypersensitivity and change in the expression of the dopamine D2 receptor by administration of anti-CGRP antibody into the trigeminal ganglion in trigeminal neuropathic pain model rats. - Hiroharu Maegawa; Nayuka Usami; Chiho Kudo; Hitoshi Niwa (PLoS ONE)
Calcitonin gene-related peptide (CGRP) and dopamine D2 receptor (D2 receptor) are associated with neuropathic pain. However, their relationship is not well understood. To better establish their relationship in trigeminal neuropathic pain, we examined male rats with infraorbital nerve (ION) ligation. Rats with ION ligation were administered CGRP or anti-CGRP antibody into the trigeminal ganglion (TG). The change in the head-withdrawal threshold was measured using von Frey filament. Immunohistochemical staining for phosphorylated extracellular signal-regulated kinase (pERK) was also performed in the trigeminal spinal subnucleus caudalis (Vc). CGRP was detected in the TG and Vc by immunohistochemical staining, and glial fibrillary acidic protein (GFAP) in the TG and dopamine D2 receptor in the Vc were detected in the same way. Antibody administration restored the head-withdrawal threshold to mechanical stimuli, which had decreased after ION ligation. Furthermore, the number of pERK-immunoreactive (-IR) neurons in the Vc, which increased following ION ligation, declined. The ratio of CGRP-IR TG neurons, large-sized CGRP-IR TG neurons, and TG neurons encircled with the GFAP-IR cells increased after ION ligation and decreased after antibody administration. Moreover, the immunoreactivity of CGRP and D2 receptor in the Vc increased after ION ligation and decreased after antibody administration. There were no significant differences in the head-withdrawal threshold, pERK-IR cell count, ratio of CGRP-IR TG neurons, ratio of size of CGRP-IR TG neurons, ratio of TG neurons encircled with GFAP-IR cells, and immunoreactivity of CGRP and D2 receptor in the Vc between the ION-ligated rats with and without CGRP. These findings suggest that the administration of an anti-CGRP antibody into the TG is involved in the suppression of trigeminal neuropathic pain and the D2 receptor expression in the Vc.